Visualization of Tawang Alun Temple Based Augmanted Reality as a Representation of Ancient Relics in Sedati Sidoarjo - Aliful Fatikh Pulunggono Suseta; Ade Eviyanti (Procedia of Engineering and Life Science, 2021)
Tawangalun Temple is one of the heritage temples of the Majapahit Kingdom in Sidoarjo Regency which is located in Buncitan Village, Sedati District. Based on the analysis of problems in the field of historical construction, Tawang temple still has little information in digital form, so that little information is visually packaged in digital, resulting in a lack of public interest in accessing information. The system development research method used is an action research research design where the research is carried out by designing the Tawang Alun Temple AR application and implementing the design. This research will create augmented reality by recommending locations that can help all people, from school children to students and the general public, displaying the Tawang Alun Temple site. This application will be able to display 3D objects in the form of the Tawang Alun temple.